2017
DOI: 10.1007/978-3-319-66179-7_18
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Pancreatic Cysts in Computed Tomography Images Using a Random Forest and Convolutional Neural Network Ensemble

Abstract: There are many different types of pancreatic cysts. These range from completely benign to malignant, and identifying the exact cyst type can be challenging in clinical practice. This work describes an automatic classification algorithm that classifies the four most common types of pancreatic cysts using computed tomography images. The proposed approach utilizes the general demographic information about a patient as well as the imaging appearance of the cyst. It is based on a Bayesian combination of the random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 13 publications
0
40
0
2
Order By: Relevance
“…The use of radiomics also appears to outperform conventional clinical and radiologic methods in discriminating between cyst types. In a study of 134 patients with a variety of histologically-confirmed PCLs, Dmitriev et al found that manually selected quantitative features (location, intensity, and shape) in preoperative CTs more accurately classified cystic lesions than conventional clinical criteria (accuracy 80% vs. 62%) [ 40 ]. This study also found that the use of convolutional neural network features performed similarly to manual quantitative features, but the combination of both reached the highest accuracy (84%).…”
Section: Radiomics To Identify Cyst Typementioning
confidence: 99%
“…The use of radiomics also appears to outperform conventional clinical and radiologic methods in discriminating between cyst types. In a study of 134 patients with a variety of histologically-confirmed PCLs, Dmitriev et al found that manually selected quantitative features (location, intensity, and shape) in preoperative CTs more accurately classified cystic lesions than conventional clinical criteria (accuracy 80% vs. 62%) [ 40 ]. This study also found that the use of convolutional neural network features performed similarly to manual quantitative features, but the combination of both reached the highest accuracy (84%).…”
Section: Radiomics To Identify Cyst Typementioning
confidence: 99%
“…Bottleneck layer (1×1 convolutional layer) before each 3×3 convolution was used to reduce the number of input feature-maps, and thus to improve computational efficiency. For comparison with traditional CNN, we designed a similar architecture as the model in [5] which specifically tailoring to pancreatic cysts classification.…”
Section: Implementation Detailsmentioning
confidence: 99%
“…Deep learning approaches such as convolutional neural networks (CNNs) have achieved superior performance in various fields such as classification, detection, segmentation, and super-resolution in images [5][6][7][8][9][10][11]. CNNs can automatically extract multilevel features, specific to the application, from images.…”
Section: Introductionmentioning
confidence: 99%